Detection of dairy products from multiple taxa in Late Neolithic pottery from Poland: an integrated biomolecular approach. Issue 3 (15th March 2023) - Evans, Miranda; Lundy, Jasmine; Lucquin, Alexandre; Hagan, Richard; Kowalski, Łukasz; Wilczyńki, Jarosław; Bickle, Penny; Adamczak, Kamil; Craig, Oliver E.; Robson, Harry K.; Hendy, Jessica
Abstract : The detection of dairy processing is pivotal to our understanding of ancient subsistence strategies. This culinary process is linked to key arguments surrounding the evolution of lactase persistence in prehistory. Despite extensive evidence indicating the presence of dairy products in ceramics in the European Neolithic, questions remain about the nature and extent of milk (and lactose) processing and consumption. In order to investigate past patterns of dairy processing, here we analyse ancient proteins identified from Late Neolithic Funnel Beaker ceramics, scrutinizing the principle that curd and whey proteins partition during the production of dairy foods from milk. Our results indicate the presence of casein-rich dairy products in these vessels suggesting the creation of curd-enriched products from raw milk. Moreover, this analysis reveals the use of multiple species for their dairy products in the Late Neolithic, adding to a growing body of evidence for the period. Alongside palaeoproteomic analysis, we applied well-established lipid residue analysis. Differential interpretations between these two approaches show that palaeoproteomics is especially useful where the effects from isotope mixing may underestimate the frequency of dairy products in archaeological ceramics, highlighting the potential utility of a multi-stranded approach to understand life histories of vessel use.